Processos oxidativos avançados aplicados no tratamento de águas de lavagem da indústria farmacêutica - Miele, Rafael Goncalves [UNIFESP] (2016)
The pharmaceutical residues are an emergent class of environmental contaminants extensively used in human and veterinary medicine. The main waste entry route into the environment is the dumping of domestic sewage, treated or not, in watercourses. In the last years, it has seen a significant development of pharmaceutical sector activities, resulting in the generation of an increasing volume of industrial effluents containing biologically active organic compounds. Thus, for treatment of such waste, the application of conventional biological process may be inadequate because some of these compounds are recalcitrant or toxic to microorganisms, requiring the development of new methods. In 2013, the European Union (EU) by Directive 2013/39/EU looked to the need for the development of innovative wastewater treatment processes and economically feasible and, in 2015, led to the inclusion of diclofenac on a watch list of substances to be monitored by all the member countries. The advanced oxidation process (AOP) may be applied as an alternative or complement to conventional wastewater treatment process, once consisting of chemical free radical generators systems, in particular hydroxyl radicals, which are formed by different chemical and photochemical mechanisms, being highly reactive, little selective, may act in the chemical oxidation of highly toxic organic pollutants. This study aimed to evaluate the degradation of higher consumption of drugs, potassium diclofenac (DCF), in aqueous medium, by simulating an effluent generated by the pharmaceutical industry ( 3,0 L volume and initial concentration of DCF equal to 100 mg C L-1), using an annular reactor, equipped with a medium pressure mercury vapor UV lamp (Hanovia 679A36, 450 W), applying some AOP?s such as photolysis (UV), photolysis of hydrogen peroxide (H2O2/UV), Fenton (Fe2+/H2O2) and photo-Fenton (Fe2+/H2O2/UV). The variables of the respective process, such as concentration of Fe2+ (0,03 to 1 mmol L-1), molar rate of addition of H2O2 (0,63 to 1,64 mmol min-1) and pH (2,5 to 7,5) were studied and compared, allowing determine the most efficient system in the treatment of simulated wastewater and optimize its variables by performing an experimental planning Doehlert. Most of literature studies investigated the degradation of DCF under pH control and thus avoiding their precipitation. The results of this study indicate that the application of photo-Fenton AOP degradation to DCF, without pH control, under certain experimental conditions, a mineralization (organic carbon converted to CO2 and H2O) in amounted to 90 %.